Manfaat Media Sosial Sebagai Alat Pemasaran bagi Pengusaha Muda di Desa Situgadung Kabupaten Tangerang - Ningsih, Dewi; Sunanto, Sunanto; Capriat, Zelin Ferdias (Jurnal PKM Manajemen Bisnis, 2025)
In today’s digital era, social media has become an essential tool for marketing, offering vast opportunities for young entrepreneurs to expand their businesses. However, many small business owners in rural areas still face challenges in effectively utilizing these platforms. This community service program aimed to empower young entrepreneurs in Situgadung Village, Tangerang Regency, by enhancing their knowledge and skills in social media marketing. The program took place in April 2025 at Situgadung Village and was facilitated by 12 lecturers from Universitas Pamulang. It involved 25 local MSME entrepreneurs as participants. The activities were carried out through a combination of lectures, practical simulations, interactive discussions, and question-and-answer sessions to maximize learning outcomes. Findings indicate that the participants improved their ability to use social media for promoting their products, engaging customers, and building their brand image. Many expressed greater confidence in managing digital marketing strategies and maintaining social media presence. This initiative contributed to raising awareness about modern marketing methods and is expected to support the growth and sustainability of the local businesses. Overall, the program demonstrates the critical role of social media as a marketing tool for young entrepreneurs in rural communities and offers a valuable framework for similar community empowerment efforts.